1987
DOI: 10.1093/nar/15.24.10551
|View full text |Cite
|
Sign up to set email alerts
|

The complete sequence of the MHC class II chain RT1Dαuof the diabetic BB rat: mRNA levels of RT1.Dα in lymphocytes

Abstract: The major histocompatibility complex of the rat (RT1 complex) encodes two sets of class II molecules referred to as RT1.B and RT1.D. The complete structure of the RT1.D alpha u chain of the diabetes prone BB rat was determined by the isolation and characterization of a full size cDNA. Comparisons of the nucleotide and protein sequences of RT1.D alpha with the analogous molecules, H-2 I-E alpha and HLA DR alpha, revealed that these alpha chains have been highly conserved during evolution. Southern blot analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…At the carbamate carbon (C10) 2,7-DAM ( 36 , Scheme ) monoalkylates DNA in the major groove at guanine N7 of (G) n tracts. , The selectivity correlates with the sequence specificity of the negative molecular electrostatic potential of the major groove, suggesting that the alkylation selectivity of 2,7-DAM is determined by sequence-specific variation of the reactivity of the DNA . This may not be surprising considering that N7 is the most nucleophilic position of guanine , and that the less reactive carbamate alkylating function has been shown to follow patterns of reactivity characteristic of S N 2 displacement. This adduct is nontoxic, and since reduction of MC in vivo or in vitro converts most of the drug to the nontoxic quinone 2,7-DAM, this process may be regarded as an additional detoxification mechanism. , …”
Section: Biochemistrymentioning
confidence: 99%
“…At the carbamate carbon (C10) 2,7-DAM ( 36 , Scheme ) monoalkylates DNA in the major groove at guanine N7 of (G) n tracts. , The selectivity correlates with the sequence specificity of the negative molecular electrostatic potential of the major groove, suggesting that the alkylation selectivity of 2,7-DAM is determined by sequence-specific variation of the reactivity of the DNA . This may not be surprising considering that N7 is the most nucleophilic position of guanine , and that the less reactive carbamate alkylating function has been shown to follow patterns of reactivity characteristic of S N 2 displacement. This adduct is nontoxic, and since reduction of MC in vivo or in vitro converts most of the drug to the nontoxic quinone 2,7-DAM, this process may be regarded as an additional detoxification mechanism. , …”
Section: Biochemistrymentioning
confidence: 99%
“…The coding region for RT1D␣ u consisted of an 881-bp Pst I fragment from the plasmid RT1.D␣ u -11. This was subcloned into the Pst I site in pcDNA3.1Zeo to generate the plasmid pZRT1.D␣ u (16). This plasmid was digested with Nru I/Pvu II, and the 1,839-bp fragment consisting of the human cytomegalovirus promoter RT1.D␣ u cDNA and SV40 polyA signal was subcloned into the Nru I site of pZRT1.D␤ u to generate the final pZRT1.D␣/␤ u plasmid.…”
Section: Plasmid Constructs and Dna Preparationmentioning
confidence: 99%
“…Fcer1g , a high‐affinity IgE receptor, is a key molecule involved in allergic reactions 36 . The proteins encoded by RT1‐DA and Ccl4 were also associated with inflammatory function 37,38 . Also, immune response and inflammatory response are the key pathological processes after SCI 28 .…”
Section: Discussionmentioning
confidence: 99%
“… 36 The proteins encoded by RT1‐DA and Ccl4 were also associated with inflammatory function. 37 , 38 Also, immune response and inflammatory response are the key pathological processes after SCI. 28 Jogia retrospectively analyzed 161 patients with SCI and found that early control of SCI‐induced systemic immune response was beneficial to longer‐term recovery.…”
Section: Discussionmentioning
confidence: 99%